Analysis of gait characteristics to evaluate injury risk after high-intensity exercise, focusing on canoe athletes: a preliminary study - Kim, S.; Son, M.; Shin, S.; Kim, T.; Choi, S. (Frontiers in Sports and Active Living, 2025)
Objective: High-intensity exercise can alter gait characteristics in canoe athletes, potentially affecting performance and increasing injury risk due to muscle fatigue. This study aimed to analyse gait parameters before and after high-intensity exercise to identify fatigue-related injury risk factors.